Pediatric Lung Abscess: A Case Report - Melissa Adriani Tjahyadi; Basaria Lidya Sinurat; Hosea Gerry Leesander; Nadya Angelica; Rini Riantie (Rumah Sakit Unggul Karsa Medika, 2023)
Lung abscess is an infection that destroys the lung parenchyma, resulting in cavity formation and central necrosis, with purulent material. Lung abscess are much less common in children, with estimated incidence at 0.7 per 100,000 admissions per year, than in adults